(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
Qualitative methods such as direct observation, key informant interviews, and focus group discussions are effective for gathering reliable information. Focus group discussions aim to elicit factual information and insights from participants, complementing sample surveys in questionnaire development and interpreting survey results. Combining focus group discussions with surveys can provide a more comprehensive assessment of topics. It is crucial to include diverse perspectives and prevent biases in discussions. Key informant interviews involve in-depth interviews with individuals with specialized knowledge or expertise on a particular topic of interest. Participant observation is a qualitative research method where the researcher immerses themselves in a social setting or group, observing and participating in the behaviors, interactions, and practices of the participants. Participant observation is a valuable qualitative research method that enables researchers to gain profound, contextual insights into social groups and phenomena by actively participating in and observing their activities over an extended period.